Enhancing Agricultural Productivity in Dairy Cow Mastitis Management: Innovations in Non-Antibiotic Treatment Technologies - Lijie Jiang; Qi Li; Huiqing Liao; Hourong Liu; Zhiqiang Wang (Veterinary Sciences, 2025)
Dairy mastitis is a common dairy farming disease. It severely affects the health of dairy cows and the quality and yield of dairy products. This paper reviews the main current mastitis treatments and associated bacterial resistance. It emphasizes the importance of integrated resistance and treatment management. The therapeutic efficacy and resistance associated with commonly used antibiotics such as penicillin, cephalosporins, macrolides and fluoroquinolones are analyzed. The principles, application effects and benefits of non-antibiotic therapies are also discussed, including those of immunotherapy, herbal therapy, probiotic therapy and phage therapy. The paper presents the latest gene editing and nanotechnology advances in the contexts of big data and artificial intelligence. It suggests future research directions such as developing new antibiotics, optimizing treatment and enhancing immunity. In conclusion, effective treatment and management can control dairy cow mastitis. It can guarantee cow health, improve dairy product quality and promote sustainable dairy industry development.